(3SYGOI GdCfGe aj COYjI GdSGYGJ hGdCjGes - (3eMeO QVG Hf bGSe Hf eMeO GdZQGhj, J (B1385(3g` (B1965(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj LYd GdOYGA eaGJjM GdfLGM (B... (3CeG GdebOeI aajgG YOI ahGFO, GdChdi aj GSJMHGH GdOYGA hGdGcKGQ efg aj LejY GdMGdGJs
(3BNQgG (B:s
(3BNQgG(B: (3hYf SdeGf GdaGQSj(B: (3eG ef YHO jbhd Mjf jUHM Ch jeSj KdGKG(B: (3GdMeO ddg QH GdYGdejf, GdMeO ddg MeOG cKjQG WjHG eHGQcG(B. (3UQa Gddg Yfg SHYjf fhYG ef GdHdGA COfGgG Gdges
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3GdCYdGe, L (B6: 128s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs